Current levels, sources, and risks of human exposure to PAHs, PBDEs and PCBs in South American outdoor air: A critical review - Akinrinade, Olumide Emmanuel [UNESP]; Rosa, André Henrique [UNESP] (Elsevier, 2025)
This study provides a comprehensive overview of the current levels, sources and human exposure risks to hazardous polycyclic aromatic hydrocarbons (PAHs), polybrominated diphenyl ethers (PBDEs), and polychlorinated biphenyls (PCBs) in South American outdoor air. Research documents were obtainable for only 6 countries within the target period (2014–2024). For all contaminants, urban concentrations exceeded that of rural/remote locations. PAHs were extensively reported with concentration reaching 1100 ∑16PAHs/m3 in Southwest of Buenos Aires province, Argentina. The health risk data also exceeded the threshold level in several locations. The profiles and seasonal fluctuations across all studies were widely influenced by the prevalent local/domestic sources. Biomass combustion (particularly of sugar cane/agricultural wastes and wood/coal for residential heating), vehicular emission, and industrial emission were accounted for most PAH sources. Regulations targeting biomass combustion for improved air quality seem not to currently have significant impacts on current PAH levels. PBDEs were widely reported within 0.3–55 pg ∑4-14BDE/m3, albeit high concentrations were documented in Concepción Bay, Chile (maximum = 1100 pg ∑4BDE/m3) and Córdoba, Argentina (maximum = 120 pg ∑4BDE/m3). Most notable source of PBDEs is solid municipal wastes. Similar to other global studies, BDE-47, 99 and 209 dominated the congeners reported. PCBs were reported with the highest concentrations measured in Córdoba, Argentina (maximum = 1700 pg ∑30PCBs/m3), but data remain limited in other important locations such as São Paulo, Brazil. Sources of PCBs were broadly associated with solid wastes, electric transformers, and re-volatilization from polluted environment. PAHs, PCBs and PBDEs were all within average to top global concentrations. This study underscores potential rise in atmospheric level of the target contaminants without sustainable regulatory structure and the need for continuous monitoring of these contaminants as a measure of policy impacts. We provide sustainable recommendations.
Keywords: Atmosphere; Flame retardants; Organo-halogenated compounds; Persistent organic pollutants; Stockholm convention